2014
DOI: 10.1074/jbc.m113.535351
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Insights into the Human Börjeson-Forssman-Lehmann Syndrome-associated Protein PHF6

Abstract: Background: PHF6 gene is mutated in BFLS and adult acute myeloid and T-cell acute lymphoblastic leukemias. Results: Crystal structure of the second extended PHD domain of PHF6 was solved. Conclusion: PHF6-ePHD2 is a novel structural module and binds dsDNA. Significance: PHF6 may function as a transcriptional repressor using its ePHD domains binding to DNA and recruiting NuRD complex through its NoLS region to regulate gene transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 50 publications
(39 reference statements)
2
72
0
1
Order By: Relevance
“…Extensive hydrophobic interactions hold the globular structure of this region, which is important for its function 12 . Phe1662 is fully buried at the core, stabilizing the structure of this PHDlike domain while Gly1652 is partially buried (Fig.…”
Section: Kmt2b Is Constrained For Missense and Predicted Protein Trunmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive hydrophobic interactions hold the globular structure of this region, which is important for its function 12 . Phe1662 is fully buried at the core, stabilizing the structure of this PHDlike domain while Gly1652 is partially buried (Fig.…”
Section: Kmt2b Is Constrained For Missense and Predicted Protein Trunmentioning
confidence: 99%
“…p.Phe1662Leu and p.Gly1652Asp occur within a PHD-like domain (residues 1574-1688), predicted to facilitate interaction with DNA, protein-protein interaction and recognition of methylated/unmethylated lysines [12][13][14] . Extensive hydrophobic interactions hold the globular structure of this region, which is important for its function 12 .…”
Section: Kmt2b Is Constrained For Missense and Predicted Protein Trunmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that residues 152-171 of PHF6 can directly interact with RBBP4 (RbAp48) in GST pulldown assays in vitro (20). ITC was conducted using a synthetic optimized PHF6 peptide (residues 157-171) to titrate RBBP4 (Fig.…”
Section: Phf6 Binds To Rbbp4/rbap48 Forming a Stable Complex-mentioning
confidence: 99%
“…Furthermore, in our previous work, we showed that the PHF6 protein can directly interact with the NuRD complex component RBBP4 and that the interaction is mediated by the nucleolar localization sequence (NoLS) composed of NLS3 and NLS4 of PHF6 (20). To study the molecular basis of this interaction, we subsequently determined the crystal structure of RBBP4 in complex with a PHF6 peptide (residues 157-171).…”
mentioning
confidence: 99%